Development of cannabis use disorder in medical cannabis users: A 9-month follow-up of a randomized clinical trial testing effects of medical cannabis card ownership - Cooke, Megan E.; Potter, Kevin W.; Jashinski, Julia; Pascale, Michael; Schuster, Randi M.; Tervo-Clemmens, Brenden; Hoeppner, Bettina B.; Pachas, Gladys N.; Evins, A. Eden; Gilman, Jodi M. (Frontiers in Psychiatry, 2023)
Background: Evidence for long-term effectiveness of commercial cannabis products used to treat medical symptoms is inconsistent, despite increasingly widespread use. Objective: To prospectively evaluate the effects of using cannabis on self-reported symptoms of pain, insomnia, anxiety, depression, and cannabis use disorder (CUD) after 12 months of use. Methods: This observational cohort study describes outcomes over 9 months following a 12-week randomized, waitlist-controlled trial (RCT: NCT03224468) in which adults (N=163) who wished to use cannabis to alleviate insomnia, pain, depression, or anxiety symptoms were randomly assigned to obtain a medical marijuana card immediately (immediate card acquisition group) or to delay obtaining a card for 12 weeks delay (delayed card acquisition group). During the 9-month post-randomization period, all participants could use cannabis as they wished and choose their cannabis products, doses, and frequency of use. Insomnia, pain, depression, anxiety, and CUD symptoms were assessed over the 9-month post-randomization period. Results: After 12 months of using cannabis for medical symptoms, 11.7% of all participants (n = 19), and 17.1% of those using cannabis daily or near-daily (n = 6) developed CUD. Frequency of cannabis use was positively correlated with pain severity and number of CUD symptoms, but not significantly associated with severity of self-reported insomnia, depression, or anxiety symptoms. Depression scores improved throughout the 9 months in all participants, regardless of cannabis use frequency. Conclusions: Frequency of cannabis use was not associated with improved pain, anxiety, or depression symptoms but was associated with new-onset cannabis use disorder in a significant minority of participants. Daily or near-daily cannabis use appears to have little benefit for these symptoms after 12 months of use.